Facilitating statistical software using SS E Guide / N. Ahmad, A.M. Nasir, and S. Masrom - N., Ahmad; A.M., Nasir; S., Masrom (Universiti Teknologi MARA, Kedah, 2019)
The process of data analysis for the purpose of research is very important and this process sometimes is very complicated, especially for researchers who do not have any statistical basis. We developed specific software to analyze the data. The problem occurs when students are not familiar with such software. The most important process in the analysis of data is to run the correct analysis. For example, analysis of mean between samples can be done either using parametric or non-parametric test. If students choose the wrong analysis, this will lead to the inappropriate conclusion. The second problem face by the students is how to use statistical software. Some software will produce output even if the method chosen is not suitable. So this E Guide application is intended to facilitate two things: how to choose the appropriate analysis data and how to use statistical software to get the correct output. E Guide also provides interpretation of output from example provided.